Enkele aspecten van primaire gezondheidszorg in een rurale streek van Zaire - De Schryver, Antoon (Afrika Focus, 1985)
Primary health care during the period 1980-1982 in the sector of Kasongo-Lunda, Zaire is considered. Health infrastructure and main health problems are discussed. These problems were mainly diarrheas, respiratory infections, malaria, tuberculosis, whooping cough, measles, malnutrition and wormrelated diseases. A vaccination programme against diphteria, tetanus, whooping cough, poliomyelitis, measles and tuberculosis was set up and adapted to W.H.O. recommendations in 1981. The incidence of measles and whooping cough declined dramatically during the period 1978-1982. Diarrhea was treated with oral rehydration. About 16% of the children under five years of age suffered from malnutrition, mostly related to worm diseases ; therefore, a suppressive dose of antihelminthics was given every three months. These results show that local health centers, concerned with everyday health problems of the population, can have a strong positive influence upon the general health situation of a rural population. KEYWORDS : primary health care, expanded programme of immunisation, measles, whooping cough, diarrhea, tuberculosis, malnutrition, wormdiseases